Choices: Volume 2 -- Charting a Positive Future for Teen Parents - Joy Cantrell Jordan; Linda B. Bobroff; Julie Copenhagen; Glenda L. Warren (EDIS, 2002)
The CHOICES curriculum is designed to help pregnant and parenting teens chart a more positive future. The curriculum recognizes that teens are still developing and have needs in addition to those of becoming a parent. It was developed through a team effort of the Department of Home Economics including the Expanded Food and Nutrition Education Program and the Department of 4-H and Other Youth Programs.